INNOVATIVE STRATEGIES FOR IMPROVING TECHNOLOGY IN PRIMARY EDUCATION FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - ABUBAKAR, ALIYU SAULAWA; EKELE, CONFORT BISSALAH (Sokoto Educational Review, 2025)
In recent years, there has been a growing recognition of the importance of integrating innovative technology strategies into primary education to foster sustainable development. This study investigates various approaches and methodologies aimed at enhancing technology use in primary schools to create a more effective and engaging learning environment. A key strategy is incorporating digital learning tools and platforms that support interactive and personalized learning experiences. These tools can cater to students' diverse needs, enabling them to learn at their own pace and according to their individual learning styles. By utilizing educational software, online resources, and gamified learning applications, educators can make learning more engaging and accessible, thus improving student motivation and outcomes. The study also reviewed the potential of teacher training and professional development programs focused on technology integration. By equipping teachers with the necessary skills and knowledge to effectively use technology in the classroom, schools can ensure that educators are well-prepared to facilitate technology-enhanced learning. This includes training in using digital tools and strategies for integrating technology into various subjects and curricula. The research highlights the importance of infrastructure and resource allocation in supporting technological advancements in primary education. Access to reliable internet, modern devices, and technical support is essential for the successful implementation of technology-based initiatives. The study suggests that investment in infrastructure, along with partnerships between governments, educational institutions, and the private sector, is crucial for creating a conducive environment for technology-driven education. DOI: https://doie.org/10.0302/SER.2025798879